Chemical quality parameters and bioactive compound content of Brazilian berries - Segantini, Daniela Mota [UNESP]; Falagán, Natalia; Leonel, Sarita [UNESP]; Modesto, Joyce Helena [UNESP]; Takata, Willian Hiroshi Suekane [UNESP]; Artés, Francisco (FapUNIFESP (SciELO), 2015)
There is a growing consumer demand for higher healthy foods such as berries which are a rich source of phenolic compounds. The current work evaluated blackberry cultivars: Cherokee, Tupy and Xavante; raspberry cultivars: Heritage, Fallgold and Black; and the hybrid Boysenberry. All berries were grown under homogenous subtropical conditions in Brazil. Black raspberry, Cherokee and Tupy blackberry cultivars showed the highest ratio between soluble solid contents and titratable acidity, and Fallgold and Heritage raspberry showed the highest titratable acidity. Total phenolic content ranged from 2.03 to 5.33 g kg−1 fresh weight and total anthocyanin content registered values from 0.41 to 1.81 g kg−1 fresh weight. The most common phenolic acids were gallic, p-coumaric and ellagic, and for anthocyanins: cyanidin-3-glucoside and malvinidin-3-glucoside. Antioxidant capacity ranged from 14.13 to 21.51 mol equivalent trolox kg−1 fresh weight. Black raspberry, all blackberry cultivars and the Boysenberry hybrid are appropriate to be consumed fresh, while Fallgold and Heritage raspberries are recommended to the food industry. Due to their phenolic richness and antioxidant properties, these fruits are of great interest to the fresh fruit market and to pharmaceutical industries. These results could help breeders and growers when planning the cultivar selection according to their foreseeable destination.
Keywords: Anthocyanins; Antioxidant capacity; Phenolics; Rubus idaeus; Rubus spp